A Case Report: Hysterectomy in Eleventh Months Infant (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Endometrial carcinoma in an infant is a very rare condition; it typically occurs in elderly patients; approximately 88% are postmenopausal at the time of diagnosis1. Classically, Endometrial carcinoma affects the obese, nulliparous, infertile, hypertensive and diabetic white women, but usually can be occur in the absence of all these factors. Estrogens are   implicated as causative factor in endometrial carcinoma because a high incidence of this disease in patients with presumed attention in oestrogen metabolism and   in those who take exogenous estrogens. Polycystic   ovarian disease and Granulosa cell tumours of the ovary can produce high level of oestrogens but are rare cause of hyperestrogenism and endometrial   carcinoma2.Gonadal dysgenesis can also be associated with endometrial adenocarcinoma3. Embrional vaginal carcinoma are most commonly   seen in very young girls. The tumour usually involves the vagina , the cervix may be affected as well, particularly in an older child. Batryoids sarcoma arises   from the submucosal tissue and rapidly spread beneath   an intact vaginal epithelium and bulges as polypoid   growth. Three types of vaginal and cervical tumour may appear during childhood & early teens,   endometrial carcinoma occur most often in young children. Carcinoma arising in a remnant of a mesonephric duct occurs more often in girls of 3 yrs   of age or older4. Clear cell adenocarcinoma of   nulliparous origin often associated with a history of antenatal exposure of DES ( Diethylestilbestrol ). But   no clear cut evidence is detected in infant or childhood   endometrial carcinoma. DOI: http://dx.doi.org/10.3329/bjog.v26i1.13760 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 45-47